Bitcoin: an alternative currency to pay for goods and services or a useful investment tool? - Rowland Zuzana; Suler Petr; Cajkovicova Bohdana (SHS Web of Conferences, 2021)
Research background: Bitcoin is defined as digital money in a peer-to-peer decentralized payment network, an amalgam hybrid between fiat and commodity currency without a real value. This digital currency is also independent of any government or currency administration. Purpose of the article: This article explores whether bitcoin works as a medium of exchange or relates to assets, focusing on its current use and future utility regarding its characteristics. Methods: Analysing bitcoin statistical features, we found no connection with traditional asset categories such as stock, bonds and commodities either in intermediate time, or periods of financial crises. Findings & Value added: The study suggests that investors’ abiding interest in bitcoins can have a positive impact on their liquidity in the real time.